Ethanol induced adaptations in 5-HT2c receptor signaling in the bed nucleus of stria terminalis: Implications for anxiety during ethanol withdrawal - Marcinkiewcz, Catherine A. (Neuropharmacology, 2014)
One of the hallmarks of alcohol dependence is the presence of a withdrawal syndrome during abstinence, which manifests as physical craving for alcohol accompanied by subjective feelings of anxiety. Using a model of chronic intermittent ethanol (CIE) vapor in mice, we investigated the role of serotonin2c signaling in the BNST as a neural substrate underlying ethanol-induced anxiety during withdrawal. Mice were subjected to a 5-day CIE regimen of 16 hours of ethanol vapor exposure followed by an 8 hour “withdrawal” period between exposures. After the 5(th) and final exposure, mice were withdrawn for 24 hours or 1 week before experiments began. Anxiety-like behavior was assessed in the social approach, light dark, and open field test with mice showing deficits in social, but not general anxiety-like behavior that was alleviated by pretreatment with the 5HT2c-R antagonist SB 242,084 (3 mg/kg, i.p.) 24 hours and 1 week post-CIE. Using immunohistochemistry and whole cell patch clamp electrophysiology, we also found that CIE increased FOS-IR and enhanced neuronal excitability in the ventral BNST (vBNST) 24 hrs into withdrawal in a 5HT2c-R dependent manner. This enhanced excitability persisted for 1 week post-CIE. We also found that mCPP, a 5HT2c/b agonist, induced a more robust depolarization in cells of the vBNST in CIE mice, confirming that 5HT2c-R signaling is upregulated in the vBNST following CIE. Taken together, these results suggest that CIE upregulates 5HT2c-R signaling in the vBNST, leading to increased excitability. This enhanced excitability of the vBNST may drive increased anxiety-like behavior during ethanol withdrawal.